Further Education in the Care of Individuals with Intellectual Disabilities: Findings from a Nationwide Online Survey in Germany - Hendrik Trescher; Peter Nothbaum (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji)
This paper presents key findings from the study "Further Education in the Care of Individuals with Intellectual Disabilities," conducted at Philipps University of Marburg, Germany, between early 2023 and 2024. The research explored various aspects of professional development in this field, with a particular focus on a nationwide online survey. The survey included 254 participants in management roles at institutions serving individuals with disabilities across Germany. A primary objective was to evaluate the demand for further education within these organizations.